IMPLEMENTASI KURIKULUM 2013 PADA PEMBELAJARAN BAHASA ARAB DI MADRASAH IBTIDAIYAH - Azkia Muharom Albantani (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2015)
The implementation of 2013 Curriculum revealed discrapencies between the curriculum program and their actual realization in the field. the approach adopted in implementing the 2013 Curriculum covered student active learning as well as process oriented approach. The objective of the research is to describe and gathering information related to the implementation of 2013 curriculum and the obstacles. The population and sample of the research is MI Pembangunan UIN Jakarta and MIN Cempaka Putih Tangerang Selatan. The design of the research is qualitative case study. The data is obtained by observing, interviewing, and analyzing the document. The result of the study shows that MI Pembangunan and MIN Cempaka Putih has implemented 2013 curriculum well based on the indicator criteria. It showed that the role of the teacher is dominated in the classroom activity.DOI: 10.15408/a.v2i2.2127